2009
DOI: 10.4269/ajtmh.2009.80.319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunoprophylactic Efficacy of Brugia malayi Transglutaminase (BmTGA) in Single and Multiple Antigen Vaccination with BmALT-2 and BmTPX for Human Lymphatic Filariasis

Abstract: An attempt was made to study the immunoprophylactic efficacy of recombinant Brugia malayi transglutaminase (BmTGA) as protein vaccine along with two other recombinant proteins, Brugia malayi abundant larval transcript-2 (BmALT-2) and Brugia malayi thioredoxin peroxidase (BmTPX), in single and multiple antigen form for human lymphatic filariasis. Parasite challenge studies in jirds exhibited protection of 30%, 69%, and 43% against BmTGA, BmALT-2, and BmTPX, respectively, in single antigen vaccination mode. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 31 publications
2
39
1
Order By: Relevance
“…Strategies to identify candidate vaccine antigens against brugian or bancroftian fi lariasis include screening expression libraries with immune sera (Freedman et al, 1989), differential screening of abundantly expressed mRNAs (Gregory et al, 2000) or by the Expressed Sequence Tag (EST) approach (Blaxter et al, 1999). These strategies have facilitated the identifi cation of several potential vaccine candidates offering varying degrees of protection against fi larial infection in animal models (Thirugnanam et al, 2007;Anand et al, 2008;Vanam et al, 2009;Dakshinamoorthy et al, 2013). Antioxidant enzymes thioredoxin (TRX), thioredoxin peroxidase (TPX), glutathione-S-transferase (GST), superoxide dismutase (SOD) and glutathione peroxidase (GPX), most of which are present in all stages of the parasite and have been involved to protect the parasites from the host are reported as promising vaccine candidates (Maizels et al, 2001;Veerapathran et al, 2009;Madhumathi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies to identify candidate vaccine antigens against brugian or bancroftian fi lariasis include screening expression libraries with immune sera (Freedman et al, 1989), differential screening of abundantly expressed mRNAs (Gregory et al, 2000) or by the Expressed Sequence Tag (EST) approach (Blaxter et al, 1999). These strategies have facilitated the identifi cation of several potential vaccine candidates offering varying degrees of protection against fi larial infection in animal models (Thirugnanam et al, 2007;Anand et al, 2008;Vanam et al, 2009;Dakshinamoorthy et al, 2013). Antioxidant enzymes thioredoxin (TRX), thioredoxin peroxidase (TPX), glutathione-S-transferase (GST), superoxide dismutase (SOD) and glutathione peroxidase (GPX), most of which are present in all stages of the parasite and have been involved to protect the parasites from the host are reported as promising vaccine candidates (Maizels et al, 2001;Veerapathran et al, 2009;Madhumathi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic peptide vaccines and B-T cell chimera's containing immunodominant regions from antigens have been developed for malaria (Nardin et al, 2001), Schistosomiasis (Arnon et al, 2000) and many other viral and parasitic diseases. Thioredoxin and transglutaminase, though being reported as promising vaccine candidates cannot be used as whole antigen due to the homology that it shares with host proteins (Kunchithapautham et al, 2003;Vanam et al, 2009;Madhumathi et al, 2010). Hence immunologically dominant B and T epitopes from these proteins were identifi ed and constructed as Multi antigen peptide on an inert lysine core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, development of vaccines as a preventive tool to control the infection is important. Earlier studies have reported the utilization of recombinant proteins as vaccine candidates for the lymphatic filariasis [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Multivalent vaccines have been proved to be efficient in protection against the parasites, since it targets more than one vital protein needed for parasite survival that may include multiple stages. Our previous studies and other groups using fi-*Corresponding author: kaliraj55@yahoo.co Unauthenticated Download Date | 5/8/18 6:58 AM Chimeric vaccine for lymphatic filariasis 469 larial antigens have proved convincingly that certain combination of antigens like ALT with venom allergen homologue (VAH) show enhanced protection in multiple mode compared to single mode vaccination (Anand et al 2008, Vanam et al 2009, Anand et al 2011, Dakshinamoorthy et al 2012. Hence, in the current study, B. malayi thioredoxin (BmTRX) and Venom Allergen Homologue (BmVAH), two potent filarial vaccine candidates were chosen to make a fusion protein construct designated as TV.…”
Section: Introductionmentioning
confidence: 99%